Interfaces of occupational health management and corporate social responsibility: a multi-centre qualitative study from Germany - Eva Kuhn; Sebastian Müller; Christoph Teusch; Grit Tanner; Marlies Schümann; Carolin Baur; Eva Bamberg; Ludger Heidbrink; Stuart McLennan; Alena Buyx (BMC, 2021)
Abstract Background The workplace has been identified as a priority setting for health promotion. There are potential advantages of systematically integrating Occupational Health Management (OHM) and Corporate Social Responsibility (CSR). However, OHM and CSR are usually overseen by different management branches with different sets of values, and there is a lack of empirical research regarding interfaces between OHM and CSR. Germany offers a particularly useful setting due to legislation requiring health to be promoted in the workplace. This study aims to examine key stakeholders' views and experiences regarding interfaces between OHM and CSR in German companies. Methods Individual semi-structured qualitative interviews were conducted with a sample of 77 German stakeholders from three different groups: experts in occupational health and corporate social responsibility from various companies (n = 35), business partners (n = 19), and various non-business partners (n = 23). Transcripts were analysed using qualitative content analysis. Results Participants identified several areas in which OHM and CSR are already interacting at strategic, structural and cultural levels, but also highlighted several barriers that undermine a more meaningful interaction. Participants reported difficulties in articulating the underlying ethical values relevant to both OHM and CSR at the strategic level. Several structural barriers were also highlighted, including a lack of resources (both financial and knowledge), and OHM and CSR departments not being fully developed or undertaken at entirely different operational levels. Finally, the missing practical implementation of corporate philosophy was identified as a critical cultural barrier to interfaces between OHM and CSR, with existing guidelines and companies' philosophies that already connect OHM and CSR not being embraced by employees and managers. Conclusions There is already significant overlap in the focus of OHM and CSR, at the structural, strategic and cultural levels in many German companies. The potential is there, both in theory and practice, for the systematic combination of OHM and CSR. The insights from this study will be useful to ensure that closer integration between both management branches is set up in a socially sustainable and ethical manner.